Balancing Benefits and Risks of Indomethacin in the Management of Antenatal Bartter Syndrome: A Case Report - Alajjuri, Omar Ala'; Samaha, Mayar Essam; Honemeyer, Ulrich; Mohammed, Ghada; Mousa, Noha A. (Frontiers in Medicine, 2022)
Background: Bartter syndrome, a very rare inherited renal tubular disorder, characterized by urinary salt wastage, hypokalemia, polyuria, and metabolic alkalosis, may manifest antenatally as severe isolated polyhydramnios. Indomethacin is known to reduce salt wastage and subsequent polyhydramnios during pregnancy; however, it reduces the Ductus Arteriosus diameter among other potential complications, such as inhibition of gastrointestinal perfusion and increasing the risk of renal toxicity. Case: A 36-year-old multigravida presented with severe isolated polyhydramnios at 30 weeks of gestation. Based on a history of a previous pregnancy affected with Bartter syndrome, indomethacin was initiated. Amniotic fluid volume and Ductus Arteriosus diameter were monitored. As evidence lacks on optimal dose and duration of indomethacin, multiple-dose adjustments were made to reduce the amniotic fluid volume while maintaining normal Ductus Arteriosus diameter. Progressive polyhydramnios led to Cesarean section at 34+ weeks of gestation resulting in a healthy fetus diagnosed with Bartter syndrome in the early neonatal period. Conclusion: We share our experience in the adjustment of the dose and duration of Indomethacin therapy in the treatment of severe polyhydramnios associated with antenatal Bartter syndrome. Amniotic fluid index, Ductus Arteriosus diameter, and umbilical artery doppler work together as key indicators to guide the success and safety of the therapy